Circulating and tissue microRNAs as a potential diagnostic biomarker in patients with thrombotic events. Issue 10 (20th March 2020) - Jafarzadeh‐Esfehani, Reza; Mostafa Parizadeh, Seyed; Sabeti Aghabozorgi, Amirsaeed; Yavari, Negar; Sadr‐Nabavi, Ariane; Alireza Parizadeh, Seyed; Ghandehari, Maryam; Javanbakht, Afsane; Rezaei‐Kalat, Afsaneh; Mahdi Hassanian, Seyed; Vojdanparast, Mohammad; Ferns, Gordon A.; et al.
Abstract: Venous and arterial thrombosis are conditions that have a considerable burden if left untreated. The hypoxia‐induced by the occluded vessel can disrupt the circulation of any organ, the cornerstone of treating thrombosis is rapid diagnosis and appropriate treatment. Diagnosis of thrombosis may be made by using laboratory tests or imaging techniques in individuals who have clinical manifestations of a thrombotic event. The use of serum micro ribonucleic acids (RNAs) has recently been applied to the diagnosis of thrombosis. These small RNA molecules are emerging as new diagnostic markers but have had very limited applications in vascular disease. Most of the articles provided various microRNAs with different levels of accuracy. However, there remains a lack of an appropriate panel of the most specific microRNA in the literature. The purpose of the present review was to summarize the existing data on the use of microRNAs as a diagnostic biomarker for venous thrombosis. Abstract : This figure illustrates the possible diagnostic role of microRNAs in detecting thrombosis alongside with other diagnostic markers.